Biomass carbon-based chemical heat storage composite material and preparation method thereof

By using plant rhizomes and leaves to burn residual ash and nanocarbon materials, and combining ultrasonic oscillation adsorption, an efficient biomass carbon-based chemical heat storage composite material was prepared, which solved the problem of difficulty in preparing lithium hydroxide and high cost. Cost reduction and energy storage effect have been achieved.

CN119242274APending Publication Date: 2025-01-03FOSHAN UNIVERSITY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211003551.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2022-08-19
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Lithium hydroxide used in existing carbon-based chemical thermal storage nanocomposites is difficult to prepare and costly, which limits the promotion of its application.

Method used

The burning residual ash of plant rhizomes and leaves is used as the raw material of metal hydroxide, and the biomass carbon-based chemical heat storage composite material is prepared through the honeycomb pore structure of nanocarbon materials and ultrasonic oscillation adsorption method, which improves energy storage density and cost-effectiveness.

Benefits of technology

Efficient use of waste is achieved, production costs are reduced, and energy storage effect is improved by increasing the surface area of ​​nanocarbon matrix and optimizing the composite method.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119242274A_ABST
    Figure CN119242274A_ABST
Patent Text Reader

Abstract

The invention discloses a biomass carbon-based chemical heat storage composite material and a preparation method thereof.The biomass carbon-based chemical heat storage composite material comprises a nano carbon matrix and a metal hydroxide attached to the nano carbon matrix, the mass ratio of the nano carbon matrix to the metal hydroxide is 30%-50%: 50%-70%, the nano carbon matrix is a polygonal matrix composed of a nano carbon material, and the metal hydroxide is a metal hydroxide. Uniform hexagonal honeycomb holes are formed in the polygonal base body; the preparation method comprises the following steps: selecting a nano carbon material, processing uniform honeycomb holes in the nano carbon material, and treating the nano carbon material in a high-temperature low-oxygen closed environment for 10-15 minutes to obtain the high-adsorbability nano carbon material for later use. According to the method, firstly, the combustion residue ash of the plant roots, stems and leaves is used as a raw material of the metal hydroxide, waste utilization is achieved, secondly, the combustion residue ash of the plant roots, stems and leaves can be obtained from straw power plants, straw heating plants and the like, more ways are achieved, convenience is achieved, and therefore the cost is greatly reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of chemical energy storage materials, and in particular to a biomass carbon-based chemical heat storage composite material and a preparation method thereof. Background Art

[0002] In recent years, due to the restrictions on carbon dioxide emissions, the use of fossil fuels has been required to be reduced. In addition to energy conservation in each process, it is also necessary to promote the use of waste heat. As a means of utilizing waste heat, it is known to use warm water heat storage below 100°C using water. However, warm water heat storage has the following disadvantages: (1) it cannot store heat for a long time due to heat loss, and (2) it requires a large amount of water due to the small sensible heat amount, making it difficult to compact the heat storage equipment. Therefore, in order to promote the use of such waste heat for people's livelihood, it is necessary to develop more efficient heat storage technology.

[0003] In view of this, chemical energy storage can solve the above problems well. For example, the Chinese patent publication number CN104194735A discloses a carbon-based chemical thermal storage nanocomposite material and its preparation method, which uses a hydroxide hydrate with high energy storage density as the matrix of the composite chemical thermal storage material, and loads it on a nano-carbon material to form a composite chemical thermal storage material, wherein the mass percentage of the nano-carbon material is 30-60%. The preparation method steps are as follows: an aqueous solution of graphene oxide is obtained by the Hummer method, a metal hydroxide hydrate is added to the aqueous solution of graphene oxide, and the obtained mixed solution is condensed and refluxed at 80°C for 1h. The carbon-based chemical thermal storage nanocomposite material is obtained by hydrothermal or ultrasonic compounding and freeze-drying.

[0004] The above patent has the following shortcomings: it uses lithium hydroxide as a metal hydroxide for composite use, but lithium is a relatively active metal, and its hydroxide is difficult to prepare and obtain, resulting in high costs. Summary of the invention

[0005] The purpose of the present invention is to solve the problem of rheumatic joint pain that most people suffer from now, and to propose a biomass carbon-based chemical heat storage composite material and a preparation method thereof.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] A biomass carbon-based chemical heat storage composite material comprises a nano-carbon matrix and a metal hydroxide attached to the nano-carbon matrix, wherein the mass ratio is 30%-50% of the nano-carbon matrix: 50%-70% of the metal hydroxide. The nano-carbon matrix is ​​a polygonal matrix composed of nano-carbon materials, and contains uniform hexagonal honeycomb holes.

[0008] As a further solution of the present invention: the nano carbon matrix is ​​any one of a regular hexahedron and a regular tetrahedron.

[0009] As a further solution of the present invention: the nano-carbon material of the nano-carbon matrix is ​​graphene.

[0010] As a further solution of the present invention: the raw material of the metal hydroxide is the combustion ash of plant roots, stems and leaves.

[0011] A method for preparing a biomass carbon-based chemical thermal storage composite material comprises the following steps:

[0012] S1: Select nano-carbon material and process uniform honeycomb holes inside it;

[0013] S2: placing the nano-carbon material in a high-temperature, low-oxygen, sealed environment for 10-15 minutes to obtain a highly adsorbable nano-carbon material for use;

[0014] S3: dissolving the burning ash of plant roots, stems and leaves in water, stirring and filtering under heating conditions;

[0015] S4: adding lime to the mixed solution and continuously stirring to maintain the temperature at room temperature;

[0016] S5: filtering the stirred mixed solution, and evaporating and crystallizing the clear filtrate to obtain metal hydroxide crystals with potassium hydroxide as the main component and doped with a small amount of boron, aluminum, and manganese hydroxides;

[0017] S6: crushing and grinding the metal hydroxide crystals into granules or powder;

[0018] S7: The crushed hydroxide is compounded with a highly adsorbable nano-carbon material to obtain a biomass carbon-based chemical heat storage composite material.

[0019] As a further solution of the present invention: in S2, the temperature of the closed environment is 200-300°C, and the ratio of the oxygen content in the gas environment to the nano-carbon material is 1 mol: 100g-150g.

[0020] As a further solution of the present invention: in S3, the heating temperature is 70-80°C, and the stirring rate is 300-500rpm.

[0021] As a further solution of the present invention: in S4, the lime can be slaked lime and quicklime. When slaked lime is used, stirring at room temperature is sufficient. When quicklime is used, the solution needs to be heat-dissipated to ensure that the temperature is maintained at 20-25°C.

[0022] As a further solution of the present invention: in S6, the diameter of the metal hydroxide after crushing is less than 0.125 mm.

[0023] As a further solution of the present invention: in S7, the hydroxide and the highly adsorbable nano-carbon material are composited by ultrasonic vibration adsorption method, and the specific steps are as follows:

[0024] S71: placing the nanocarbon material in a sealed container, and gradually adding metal hydroxide from the top of the sealed container;

[0025] S72: Ultrasonic coverage is applied to the sealed container area to give it a certain microscopic vibration;

[0026] S73: lowering the composite environment to -80 to -100 degrees Celsius;

[0027] S74: Wait until there is no powder or granular floating matter in the container by naked eye observation.

[0028] The beneficial effects of the present invention are:

[0029] 1. The present invention firstly uses the combustion residual ash of plant roots, stems and leaves as the raw material of metal hydroxide, thus realizing waste utilization. Secondly, the combustion residual ash of plant roots, stems and leaves can be obtained from straw power plants, straw heating plants, etc., which has many convenient ways, thereby realizing a substantial reduction in cost.

[0030] 2. The present invention, by configuring the nano-carbon matrix to be a regular tetrahedron or a regular hexahedron with honeycomb holes disposed therein, can greatly increase its surface area, thereby increasing the carrying capacity of the metal hydroxide and increasing its energy storage effect.

[0031] 3. The present invention adopts the ultrasonic vibration adsorption method for compounding, and the metal hydroxide is sprinkled at the top, so that it can enter the honeycomb pores of the nano-carbon material to complete the adsorption, thereby increasing the compounding effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a schematic diagram of the process of a biomass carbon-based chemical thermal storage composite material proposed in the present invention. DETAILED DESCRIPTION

[0033] The technical solution of this patent is further described in detail below in conjunction with specific implementation methods.

[0034] The embodiments of the present invention are described in detail below, which are only used to explain the present invention and should not be construed as limiting the present invention.

[0035] Example 1

[0036] A biomass carbon-based chemical heat storage composite material comprises a nanocarbon matrix and a metal hydroxide attached to the nanocarbon matrix, wherein the mass ratio is 30%-50% of the nanocarbon matrix: 50%-70% of the metal hydroxide. The nanocarbon matrix is ​​a polygonal matrix composed of nanocarbon material, and the polygonal matrix contains uniform hexagonal honeycomb holes. In this embodiment, the specific shape of the polygonal matrix is ​​not limited, and it can be any one of a regular hexahedron and a regular tetrahedron, and can also be determined based on actual conditions. Preferably, the nanocarbon matrix is ​​a regular hexahedron.

[0037] The nano-carbon material of the nano-carbon matrix is ​​graphene.

[0038] The raw material of the metal hydroxide is the residual ash from the combustion of plant roots, stems and leaves.

[0039] Embodiment 2:

[0040] A biomass carbon-based chemical heat storage composite material comprises a nanocarbon matrix and a metal hydroxide attached to the nanocarbon matrix, wherein the mass ratio is 30%-50% of the nanocarbon matrix: 50%-70% of the metal hydroxide. The nanocarbon matrix is ​​a polygonal matrix composed of nanocarbon material, and the polygonal matrix contains uniform hexagonal honeycomb holes. In this embodiment, the specific shape of the polygonal matrix is ​​not limited, and it can be any one of a regular hexahedron and a regular tetrahedron, and can also be determined based on actual conditions. Preferably, the nanocarbon matrix is ​​a regular tetrahedron.

[0041] The nano-carbon material of the nano-carbon matrix is ​​graphene.

[0042] The raw material of the metal hydroxide is the residual ash from the combustion of plant roots, stems and leaves.

[0043] Embodiment 3:

[0044] A biomass carbon-based chemical heat storage composite material comprises a nanocarbon matrix and a metal hydroxide attached to the nanocarbon matrix, wherein the mass ratio is 30% of the nanocarbon matrix: 70% of the metal hydroxide. The nanocarbon matrix is ​​a polygonal matrix composed of nanocarbon material, and the polygonal matrix contains uniform hexagonal honeycomb holes. In this embodiment, the specific shape of the polygonal matrix is ​​not limited, and it can be any one of a regular hexahedron and a regular tetrahedron, and can also be determined based on actual conditions. Preferably, the nanocarbon matrix is ​​a regular hexahedron.

[0045] The nano-carbon material of the nano-carbon matrix is ​​graphene.

[0046] The raw material of the metal hydroxide is the residual ash from the combustion of plant roots, stems and leaves.

[0047] Embodiment 4:

[0048] A biomass carbon-based chemical heat storage composite material comprises a nanocarbon matrix and a metal hydroxide attached to the nanocarbon matrix, wherein the mass ratio is 50% nanocarbon matrix: 50% metal hydroxide, wherein the nanocarbon matrix is ​​a polygonal matrix composed of nanocarbon material, and the polygonal matrix contains uniform hexagonal honeycomb holes; in this embodiment, the specific shape of the polygonal matrix is ​​not limited, and may be any one of a regular hexahedron and a regular tetrahedron, and may also be determined based on actual conditions, and preferably: the nanocarbon matrix is ​​a regular hexahedron.

[0049] The nano-carbon material of the nano-carbon matrix is ​​graphene.

[0050] The raw material of the metal hydroxide is the residual ash from the combustion of plant roots, stems and leaves.

[0051] Embodiment 5:

[0052] A biomass carbon-based chemical heat storage composite material comprises a nanocarbon matrix and a metal hydroxide attached to the nanocarbon matrix, wherein the mass ratio is 40% of the nanocarbon matrix: 60% of the metal hydroxide. The nanocarbon matrix is ​​a polygonal matrix composed of nanocarbon material, and the polygonal matrix contains uniform hexagonal honeycomb holes. In this embodiment, the specific shape of the polygonal matrix is ​​not limited, and it can be any one of a regular hexahedron and a regular tetrahedron, and can also be determined based on actual conditions. Preferably, the nanocarbon matrix is ​​a regular hexahedron.

[0053] The nano-carbon material of the nano-carbon matrix is ​​graphene.

[0054] The raw material of the metal hydroxide is the residual ash from the combustion of plant roots, stems and leaves.

[0055] The present invention: firstly, the combustion residual ash of plant roots, stems and leaves is used as the raw material of metal hydroxide, thereby realizing waste utilization; secondly, the combustion residual ash of plant roots, stems and leaves can be obtained from straw power plants, straw heating plants, etc., which has many ways and is relatively convenient, thereby realizing a significant reduction in cost; in addition, the present invention can greatly increase its surface area by arranging the nano-carbon matrix into a regular tetrahedron or a regular hexahedron with honeycomb holes arranged therein, thereby increasing the carrying capacity of the metal hydroxide and increasing its energy storage effect.

[0056] Embodiment 6:

[0057] A method for preparing a biomass carbon-based chemical thermal storage composite material comprises the following steps:

[0058] S1: Select nano-carbon material and process uniform honeycomb holes inside it;

[0059] S2: placing the nano-carbon material in a high-temperature, low-oxygen, sealed environment for 10-15 minutes to obtain a highly adsorbable nano-carbon material for use;

[0060] S3: dissolving the burning ash of plant roots, stems and leaves in water, stirring and filtering under heating conditions;

[0061] S4: adding lime to the mixed solution and continuously stirring to maintain the temperature at room temperature;

[0062] S5: filtering the stirred mixed solution, and evaporating and crystallizing the clear filtrate to obtain metal hydroxide crystals with potassium hydroxide as the main component and doped with a small amount of boron, aluminum, and manganese hydroxides;

[0063] S6: crushing and grinding the metal hydroxide crystals into granules or powder;

[0064] S7: The crushed hydroxide is compounded with a highly adsorbable nano-carbon material to obtain a biomass carbon-based chemical heat storage composite material.

[0065] In S2, the temperature of the closed environment is 200-300°C, and the ratio of the oxygen content in the gas environment to the nano-carbon material is 1 mol: 100g-150g.

[0066] In S3, the heating temperature is 70-80°C, and the stirring rate is 300-500 rpm.

[0067] In S4, the lime can be slaked lime or quicklime. When slaked lime is used, stirring at room temperature is sufficient. When quicklime is used, the solution needs to be heat-dissipated to ensure that the temperature is maintained at 20-25°C.

[0068] In the S6, the diameter of the metal hydroxide after crushing is less than 0.125 mm.

[0069] In S7, the hydroxide and the highly adsorbable nano-carbon material are composited by ultrasonic vibration adsorption method, and the specific steps are as follows:

[0070] S71: placing the nanocarbon material in a sealed container, and gradually adding metal hydroxide from the top of the sealed container;

[0071] S72: Ultrasonic coverage is applied to the sealed container area to give it a certain microscopic vibration;

[0072] S73: lowering the composite environment to -80 to -100 degrees Celsius;

[0073] S74: Wait until there is no powder or granular floating matter in the container by naked eye observation.

[0074] In this embodiment, potassium carbonate and other metal carbonates in the straw ash are programmed into a metal hydroxide solution by adding lime, and then evaporated-crystallized-crushed-compounded to prepare the energy storage material; this method uses ultrasonic vibration adsorption to compound, and the metal hydroxide is sprinkled from the top, which can enter the honeycomb pores of the nanocarbon material to complete the adsorption, thereby increasing the compounding effect.

[0075] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A biomass carbon-based chemical thermal storage composite material, characterized in that: It includes a nano carbon matrix and metal hydroxide attached to the nano carbon matrix, with a mass ratio of 30%-50% of the nano carbon matrix to 50%-70% of the metal hydroxide. The nano carbon matrix is ​​a polygonal matrix composed of nano carbon materials and contains uniform hexagonal honeycomb holes.

2. The biomass carbon-based chemical thermal storage composite material according to claim 1, characterized in that: The nano carbon matrix is ​​any one of a regular hexahedron and a regular tetrahedron.

3. The biomass carbon-based chemical thermal storage composite material according to claim 1, characterized in that: The nano-carbon material of the nano-carbon matrix is ​​graphene.

4. The biomass carbon-based chemical thermal storage composite material according to claim 1, characterized in that: The raw material of the metal hydroxide is the residual ash from the combustion of plant roots, stems and leaves.

5. A method for preparing a biomass carbon-based chemical thermal storage composite material, which is the method for preparing a biomass carbon-based chemical thermal storage composite material according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1: Select nano-carbon material and process uniform honeycomb holes inside it; S2: placing the nano-carbon material in a high-temperature, low-oxygen, sealed environment for 10-15 minutes to obtain a highly adsorbable nano-carbon material for use; S3: dissolving the burning ash of plant roots, stems and leaves in water, stirring and filtering under heating conditions; S4: adding lime to the mixed solution, stirring continuously, and maintaining the temperature at room temperature; S5: filtering the stirred mixed solution, and evaporating and crystallizing the clear filtrate to obtain metal hydroxide crystals with potassium hydroxide as the main component and doped with a small amount of boron, aluminum, and manganese hydroxides; S6: crushing and grinding the metal hydroxide crystals into granules or powder; S7: The crushed hydroxide is compounded with a highly adsorbable nano-carbon material to obtain a biomass carbon-based chemical heat storage composite material.

6. The method for preparing a biomass carbon-based chemical thermal storage composite material according to claim 5, characterized in that: In S2, the temperature of the closed environment is 200-300°C, and the ratio of the oxygen content in the gas environment to the nano-carbon material is 1 mol: 100g-150g.

7. The method for preparing a biomass carbon-based chemical thermal storage composite material according to claim 5, characterized in that: In S3, the heating temperature is 70-80°C, and the stirring rate is 300-500 rpm.

8. The method for preparing a biomass carbon-based chemical thermal storage composite material according to claim 5, characterized in that: In S4, the lime can be slaked lime or quicklime. When slaked lime is used, stirring at room temperature is sufficient. When quicklime is used, the solution needs to be heat-dissipated to ensure that the temperature is maintained at 20-25°C.

9. The method for preparing a biomass carbon-based chemical thermal storage composite material according to claim 5, characterized in that: In the S6, the diameter of the metal hydroxide after crushing is less than 0.125 mm.

10. The method for preparing a biomass carbon-based chemical thermal storage composite material according to claim 5, characterized in that: In S7, the hydroxide and the highly adsorbable nano-carbon material are composited by ultrasonic vibration adsorption method, and the specific steps are as follows: S71: placing the nanocarbon material in a sealed container, and gradually adding metal hydroxide from the top of the sealed container; S72: Ultrasonic coverage is applied to the sealed container area to give it a certain microscopic vibration; S73: lowering the composite environment to -80 to -100 degrees Celsius; S74: Wait until there is no powder or granular floating matter in the container by naked eye observation.

Citation Information

Patent Citations

  • Carbon-based chemical heat storage nano-composite material and preparation method thereof

    CN104194735A